Penerapan Konsep Gamification Pada Pembelajaran Aksara Jawa SMP Kelas VIII BERBASIS ANDROID - Sunaryo, Iqbal Faturohman; Sagirani, Tri; Widana Putra, I Gusti Ngurah Alit (Jurnal Sistem Informasi Universitas Dinamika, 2021)
SMP Negeri 20 Surabaya is one of the State Junior High Schools in Surabaya. This school has several subjects, one of which is Javanese which is a local content subject that must be in school. The school has several problems, namely student learning outcomes are unsatisfactory, many students do not meet the Minimum Completeness Criteria (KKM) during exams, students tend to be passive, not a few students do not pay attention when the teaching and learning process takes place. . The solution applied to overcome this problem is to create an Android-Based Android-Based Java Script Learning Application for Middle School VIII with the Gamification Method used to facilitate student learning. The application has 3 users, namely the admin who can operate all the features, the teacher conducts an assessment, uploads material and creates questions, and students answer questions. Based on the test results using the usability scale system, the Grade Scale